Consumer behavior of Millennials in Czech Republic when facing multiple crises : experiences from the COVID-19 pandemic and the 2022 energy crisis - Rodriguez Esponda, Franco Eduardo; Kottika, Efthymia, 1982-; Vinš, Marek; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The current thesis aimed to investigate whether the consumer behavior of millennials living in the Czech Republic was affected by the COVID-19 pandemic and the 2022 energy crisis. A qualitative approach, specifically the thematic analysis, and in-depth interviews were chosen to explore and reveal changes in behavior. The findings of the study showed a clear shift from physical to online stores as a result of the anti-pandemic measures and a decline in consumption due to the reduction of the disposable income at the beginning of the pandemic. After the lockdowns and restrictions were lifted, the consumption recovered, as the use of services such as restaurants and bars increased. The 2022 energy crisis caused a consistent rise in inflation, and prices of goods and utilities increased, while consumption dropped again. Overall, the findings of this research revealed that the impact of these crises on the economy affected millennials’ decision-making, and thus consumer habits. Subsequently, recommendations to businesses to cope with this kind of scenarios were provided.
Vedoucí práce: Efthymia Kottika
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses